Hydrology and Sedimentology Study of Badr Area- NW Libyaand its Tectonic Implications - Najar, Isam M.Salih; Alhadiathy, Abdulhameed; Jasim, Ammar Abd (Iraqi Journal of Science, 2026)
The Badr area is part of the Jifarah plain at the northern escarpment of Jabal-Nafusah, northwest of Libya. According to hydrological information, groundwater depths in the area under study range between 200 in the south and 130 m in the north. However, this information did not indicate the stratigraphic sequences and nature of the groundwater layers. Geological and hydrological information was collected from 33 wells in the area to investigate this. The wells information revealed the existence of two aquifers. The first shallow aquifer lies between 16-25m depth within silty sand sediments. The second aquifer lies between 60-90m depth. In some wells (located near the present valleys and have sandy clay lithology), this aquifer has low salinity & high rate of discharge. In other wells (located away from the present valleys and have evaporitic mud lithology), it has high salinity & low rate of discharge. These differences have been interpreted to be related to multiple stages of uplift and erosion that occurred in Jabal-Nafusah during its tectonic history and to the difference in sizes & lengths of valleys, which cause additional variations in the sediments & groundwater nature. Through this study, a subsurface fault along Jabal-Nafusah and ancient valley sites has been deduced.